Studi Keharaan Tanaman dan Evaluasi Kesuburan Tanah di Lahan Pertanaman Jeruk Desa Cenggiling, Kecamatan Kuta Selatan - KETUT DHARMA SUSILA (Agrotrop : Journal on Agriculture Science, 2013)
Study on Plant Nutrient and Soil Fertility Evaluation in Citrus Plantation Land at CenggilingVillage, South Kuta District. The objective of the research to elaborate some soil chemical propertiesand classify soil fertility status of citrus plantation lands at Cenggiling Village, South Kuta District. Soilsurvey method and quantitative measurement of some soil fertility elements in laboratory based onBogor Soil Research Center procedure (1995) was done to determined criteria and soil fertility status.The result of study showed that C1 location at “subak abian” Tanijaya have chemical properties namely:CEC; base saturation; P205; K20 and C-organic are 26.13 me/100g (high criteria); 89.18% (highcriteria); 44.20 mg/100g (high criteria); 57.80 mg/100g (high criteria) and 2.51% (medium criteria)respectively with high soil fertility status. On the other hand, C2 location at “subak abian” Selondinghave chemical properties namely: CEC; base saturation; P205; K20 and C-organic are 23.40 me/100g(medium criteria); 79.36% (high criteria); 35.28 mg/100g (medium criteria); 56.35 mg/100g (highcriteria) and 1.66% (low criteria) respectively with low soil fertility status. The last, C3 location at“subak abian” Puluk-puluk have chemical properties namely: CEC; base saturation; P205; K20 and Corganicare 17.80 me/100g (medium criteria); 87.05% (high criteria); 29.37mg/100g (medium criteria);57.91 mg/100g (high criteria) and 1.54% (low criteria) respectively with low soil fertility status.